(untitled) (Research, Society and Development, 2022)
Given the increasing financialization of human life, people need to be increasingly able to manage money as a resource. Personal finance management transcends economic issues and can be discussed from the sustainability perspective in three pillars. The field of research in financial education and sustainability is remarkably recent, bringing the need to analyze the research trajectory in the area. This research is a bibliometric analysis, supported by the software VOSviewer and CitNetExplorer, and explored the course of studies in financial education and sustainability in terms of productivity by year, authors, periodicals, institutions, notable works, and words key. The main results found were that since 2011 there had been an exponential growth in publications in the area, with the United States being the country that contributed most to the field. The main research titles are related to the didactics of financial education, and the themes are more related to the social and economic spheres of sustainability. Even when composing one of the search filters in the portfolio, sustainability is still an incipient aspect when working in financial education, especially in the environmental sphere. All of this brings the need to understand the relationship between personal finance management and sustainability fully.